2016
DOI: 10.1088/1742-6596/728/7/072012
|View full text |Cite
|
Sign up to set email alerts
|

New DSH planetary nebulae and candidates from optical and infrared surveys

Abstract: On the applicability of Sato's equation to capacitative radiofrequency sheaths J Balakrishnan and G R Nagabhushana -Investigation of Al x Ga 1-x As injection heterolasers emittingvisible radiation R Altynbaev, L M Dolginov, L V Druzhinina et al. -The invariance of DSHs and DVHs under bladder filling changes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Because of the lack of WISE measurements, a search for a far-IR excess was not possible for the four other stars. In the (W2−W3), (W3−W4) diagram, the WISE colors of J1556 agree with the bulk of PNe (Kronberger et al 2014). However, as mentioned above, no nebular emission lines are visible in the SDSS spectrum (total exposure time ≈2.25 h).…”
Section: Search For Nebular Lines and Infrared Excesssupporting
confidence: 67%
“…Because of the lack of WISE measurements, a search for a far-IR excess was not possible for the four other stars. In the (W2−W3), (W3−W4) diagram, the WISE colors of J1556 agree with the bulk of PNe (Kronberger et al 2014). However, as mentioned above, no nebular emission lines are visible in the SDSS spectrum (total exposure time ≈2.25 h).…”
Section: Search For Nebular Lines and Infrared Excesssupporting
confidence: 67%
“…The latter source is indicated in the SIMBAD data base 1 as a planetary nebula. For both nebulae we found optical counterparts in the Isaac Newton Telescope (INT) Photometric Hα Survey of the Northern Galactic Plane (IPHAS; Drew et al 2005), which are indicated as circumstellar matter in the Hong Kong/AAO/Strasbourg Hα (HASH) planetary nebula database (Parker, Bojičić & Frew 2016; see also Kronberger et al 2016), and named there as PNG 117.4−01.5 (or Pa 58) and PNG 035.1+02.0, respectively. WS29 is also discernable in the Digitized Sky Survey II (DSS-II; McLean et al 2000) red band image and is a known source of radio emission (Condon, Kaplan & Terzian 1999 Figure 1.…”
Section: Two Wise Nebulae and Their Central Starsmentioning
confidence: 99%
“…• Broadband photographic imagery e.g. Abell (1966), and the recent work by the Deep-Sky Hunters (DSH) team, an amateur-professional consortium (Jacoby et al 2010;Kronberger et al 2016, and references therein). Candidates were typically identified from direct inspection of images, or the online scanned data in the case of the DSH discoveries.…”
Section: Detection Techniques Past and Presentmentioning
confidence: 99%
“…Since the last IAUS review in 2011 (Parker et al 2012), over 750 PNe and PN candidates have been found, many still needing assessment in the HASH database. Sabin et al (2014) announced the discovery of 159 true, likely and possible PNe, 284 PN candidates have been found from UWISH2 (Froebrich et al 2015; Gledhill, these proceedings), and another 180 from the DSH team and related efforts (Kronberger et al 2016;and personal communication;Acker et al 2015). Fragkou et al (2016) have found 70 candidates using radio and IR surveys, and other contributions in the infrared have been made by Flagey et al (2014), Nowak et al (2014), and Ingallinera et al (2014aIngallinera et al ( ,b, 2016 who are systematically investigating the 300+ unidentified MIPSGAL nebulae found by Mizuno et al (2010), though most remain un-assessed at the time of writing.…”
Section: Detection Techniques Past and Presentmentioning
confidence: 99%